Implementing eLearning As Edutainment in Malaysian Higher Education: Challenges and Solution for Educators - Cheong, Desmond Cheah Swee; Yusup, Hashim (2023)
Edutainment is how the teaching and learning are done in a fun and relaxed environment through strategies such as storytelling, simulations, or games. It was realized that e-learning as an edutainment approach is relatively new in Malaysia’s educational system. Hence, this study intends to investigate the challenges and solutions to the implementation of e-learning as an edutainment approach among educators of higher educational level. The study also analyzes the association between the educators’ demographic data with their perceived challenges towards the implementation of e-learning as edutainment approach. A quantitative study was conducted by a set of questionnaires to be distributed to the educators. A sample size of 170 educators from 5 colleges in Kuala Lumpur, Malaysia were chosen through a random sampling technique. Study found that the perceived challenges (M=4.32) and the perceived solutions to overcome the challenges towards the implementation of e-learning as edutainment (M=4.15) are both at high level. Through Chi Square test, it was discovered that the educators’ gender, age, and teaching experience are significantly associated with the perceived challenges in the implementation of e-learning as edutainment approach. In conclusion, e-learning through edutainment approach can be effective as the teaching and learning strategy if the educators know how to overcome its challenges. This study has implications on educators by giving them various solutions to overcome the challenges associated with the implementation of e-learning as an edutainment approach.